Literature Study: The Effect of Cold Water Immersion and Sport Massage Techniques on Muscle Pain - Afandi, Nur Rizal; Kushartanti, BM Wara; Hafidz, Abdul; Chen, Hocheng (Faculty of Sport and Health Sciences, 2023)
Pain is the most common symptom of sports injuries. Studies suggest that sports massage and or cold-water immersion may improve pain. This study aimed to synthesize findings from previous research on sports massage and cold water immersion for pain treatment in athletes. Relevant article search method using the Garuda database, Onesearch, and Google Scholar originating from sinta 2 - 3 indexed journals with the keywords